PENGGUNAAN VOKOSCREEN SEBAGAI VIDEO BELAJAR DENGAN KETERAMPILAN BERBICARA BAHASA INGGRIS DALAM E-LEARNING - Chusnul Chotimah; Nurul Hasanah Fajaria (Akademika : Jurnal Teknologi Pendidikan, 2021)
The goal of this study is to find out to what extent the Use of Vokoscreen as a Learning Video on students’ speaking skill in E-Learning at SMP Yapidh district Jati Asih. This research used descriptive qualitative method. The participants are 35 students on grade IX at SMP Yapidh. These students are chosen because they would have practical examination. The instruments are observation and interview. The result showed that the most students answered paid attention to the researchers’ explanation, they used vokoscreen application well, they joined actively in learning activity, they made an interesting presentation based on a topic, felt happy using vokoscreen as a learning video, and more confident in speaking English activity. Only a few students could not maximal in this learning because their internet connection and some private problems. The interview result showed that all students said positive answer about their opinion used vokoscreen application on speaking activity. There are 35 participants answered “like” and 2 participants answered dislike. Based on the results of this investigate could conclude that the foremost students on grade nineth at SMPIT Yapidh are propelled and appreciated on speaking activity in e-learning using vokoscreen as learning video, in reality the result of this inquire about demonstrated that the students more certainty and incremen their briefly speaking English.